Pengaruh Model Role Playing Terhadap Keaktifan Belajar Pendidikan Agama Kristen Dan Budi Pekerti Siswa Kelas VIII SMP Negeri 2 Sipoholon Tahun Pembelajaran 2023/2024 - Septiara Nengsi Simamora; Damayanti Nababan; Oloria Malau; Masniar H.Sitorus; Malani Simanungkalit (JURNAL PENDIDIKAN DAN ILMU SOSIAL (JUPENDIS), 2023)
The aim of this research is to find out how much positive and significant influence the Role Playing Model has on the active learning of Christian Religious Education and Character Education for class VIII students at SMP Negeri 2 Sipoholon for the 2023/2024 academic year. The method used in this research uses quantitative methods. The population is all 120 students in class VIII of SMP Negeri 2 Sipoholon for the 2023/2024 academic year who are Christians and the sample was determined to be 48 people, namely 40% of the total population using random sampling techniques. Data was collected using 47 positive closed items. The results of data analysis show that there is a positive and significant influence of the Role Playing Model on the learning activity of Christian Religious Education and Characteristics of class VIII students of SMP Negeri 2 Sipoholon for the 2023/2024 Academic Year: 1) Test the analysis requirements: a) test a positive relationship to obtain a score rxy = 0.561 > rtable(a=0.05,n=48) = 0.284, thus it is known that there is a positive relationship between variable .05,dk=n-2=46)= 2.021, thus there is a significant relationship between variable The regression equation Y ̂="20.68"+0.74X is obtained. Thus Ha is accepted and H0 is rejected.